DIFFERENCES IN STUDENTS' MATHEMATICS LEARNING OUTCOMES BETWEEN OFFLINE AND ONLINE LEARNING AT SMP NEGERI 2 PALU - Rifka Rifka; Muh. Rizal; Muhammad Hasbi; Welly M. (USN Kolaka, 2023)
This research aims to determine whether there are differences in student mathematics learning outcomes between offline and online learning at SMP Negeri 2 Palu. The research used a comparative method with a population of all students in class VIII, totalling 332 students. The sample was class VIII students who did offline and online learning, with different samples but the same abilities. The sampling technique is Purposive Sampling. The researchers took 60 samples consisting of 30 students each from classes A and B. The data collection technique was carried out by taking the even semester midterm test scores for the 2021/2022 academic year obtained by students during online learning and the even semester midterm test scores for the 2022/2023 academic year obtained by students during offline learning, with the same subject matter, namely the Pythagorean theorem. Provided that the material taught is equivalent during offline and online learning and has the same academic abilities: (1). Mathematics learning outcomes obtained an average score of 64.13 and 68.27 (2). Sig value. (2-tailed) 0.187 > 0.05. This means that H0 is accepted, and Ha is rejected. So, the research results show no difference in student mathematicslearning outcomes between offline and online learning.